2012
DOI: 10.1097/jcp.0b013e31825d6c25
|View full text |Cite
|
Sign up to set email alerts
|

Agomelatine Versus Venlafaxine XR in the Treatment of Anhedonia in Major Depressive Disorder

Abstract: The primary aim of the present study was to compare the effects of agomelatine (AGO) and venlafaxine XR (VLX) on anhedonia in patients with major depressive disorder. Secondary end points were to test its antidepressant and anxiolytic efficacy.Sixty patients were enrolled and randomly assigned to two different treatments: AGO (25-50 mg/d; n = 30 subjects) or VLX (75-150 mg/d, n = 30 subjects). Psychopathological assessment was performed at baseline and after 8 weeks of treatment with the Snaith Hamilton Rating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
64
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(73 citation statements)
references
References 27 publications
5
64
0
4
Order By: Relevance
“…In clinical trials, therapeutic efficacy of AGO is increased relative to placebo in moderate to severe depression (Kennedy et al, 2014). When the core symptom/domain of interest-pleasure was measured using a self-report questionnaire, in depressed patients efficacy of AGO on anhedonia was increased relative to venlafaxine Martinotti et al, 2012). In terms of operant tests of reward processing, whilst there are no published studies with AGO to-date, a 5-HT 2C antagonist compound was demonstrated to improve reversal learning, in part by decreasing perseveration, in a rat model (Boulougouris et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In clinical trials, therapeutic efficacy of AGO is increased relative to placebo in moderate to severe depression (Kennedy et al, 2014). When the core symptom/domain of interest-pleasure was measured using a self-report questionnaire, in depressed patients efficacy of AGO on anhedonia was increased relative to venlafaxine Martinotti et al, 2012). In terms of operant tests of reward processing, whilst there are no published studies with AGO to-date, a 5-HT 2C antagonist compound was demonstrated to improve reversal learning, in part by decreasing perseveration, in a rat model (Boulougouris et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The circadian pacemaker or biological clock, located in the suprachiasmatic nuclei (SCN) of the anterior hypothalamus, above the optic chiasma, is the site of generation of circadian rhythms and prepares the organism to anticipate the daily changes in the environment (6). The activation ofmelatonergic MTl receptors directly inhibits firing of neurons in the SCN, thus regulating the amplitude of the circadian rhythmicity, and facilitating sleep promotion, whereas melatonin-mediated activation of MT2 receptors is responsible for inducing phase shifts and, therefore, may be involved in the entrainment of circadian rhythmicity (7)(8)(9).…”
mentioning
confidence: 99%
“…1, 2, 3, 9), социальной активности (п.п. 7,8,13,14), эмоциональной вовлеченности (п.п. 5,6,11,12) и еды/питья (п.п.…”
Section: материал и методыunclassified
“…В сравнительных исследованиях [6,7] было показано, что агомелатин в дозе 25-50 мг в сутки более эффективен в отношении симптомов ангедонии, чем венлафаксин.…”
unclassified